Full‐3‐D tomography for crustal structure in Southern California based on the scattering‐integral and the adjoint‐wavefield methods. Issue 8 (14th August 2014) - Lee, En‐Jui; Chen, Po; Jordan, Thomas H.; Maechling, Phillip B.; Denolle, Marine A. M.; Beroza, Gregory C.
Abstract We have successfully applied full‐3‐D tomography (F3DT) based on a combination of the scattering‐integral method (SI‐F3DT) and the adjoint‐wavefield method (AW‐F3DT) to iteratively improve a 3‐D starting model, the Southern California Earthquake Center (SCEC) Community Velocity Model version 4.0 (CVM‐S4). In F3DT, the sensitivity (Fréchet) kernels are computed using numerical solutions of the 3‐D elastodynamic equation and the nonlinearity of the structural inversion problem is accounted for through an iterative tomographic navigation process. More than half‐a‐million misfit measurements made on about 38, 000 earthquake seismograms and 12, 000 ambient‐noise correlagrams have been assimilated into our inversion. After 26 F3DT iterations, synthetic seismograms computed using our latest model, CVM‐S4.26, show substantially better fit to observed seismograms at frequencies below 0.2 Hz than those computed using our 3‐D starting model CVM‐S4 and the other SCEC CVM, CVM‐H11.9, which was improved through 16 iterations of AW‐F3DT. CVM‐S4.26 has revealed strong crustal heterogeneities throughout Southern California, some of which are completely missing in CVM‐S4 and CVM‐H11.9 but exist in models obtained from previous crustal‐scale 2‐D active‐source refraction tomography models. At shallow depths, our model shows strong correlation with sedimentary basins and reveals velocity contrasts across major mapped strike‐slip and dip‐slip faults. At middle to lower crustal depths, structural features in our model may provide new insights into regional tectonics. When combined with physics‐based seismic hazard analysis tools, we expect our model to provide more accurate estimates of seismic hazards in Southern California.